Optimized equivalent circuit models for series-parallel configurations of piezoelectric transducers in energy harvesting. - Martin Moreno; Joel A Morales-Viscaya; M Xavier Cuevas-Gayosso; Juan G Parada-Salado; Francisco J Perez-Pinal (PLoS ONE)
This paper presents a detailed study of equivalent circuit models for series-parallel configurations of piezoelectric transducers used in Energy Harvesting (EH) applications. Optimizing these configurations is essential for enhancing the efficiency and performance of Piezoelectric Energy Harvesting (PEH) systems, which are increasingly employed to power small devices and sensors. The effectiveness of series-parallel configurations is demonstrated by their ability to improve the performance of the PEH system by accurately capturing system behavior across varying frequencies and load resistances. The proposed model offers a robust framework for designing and optimizing EH systems, improving the accuracy and performance of piezoelectric transducers in both series and parallel configurations. The key contribution of this work is the enhanced equivalent circuit models for PEHs, which incorporate series, parallel, and series-parallel configurations while decoupling mechanical and electrical. The models are validated through experimentation, providing a practical solution with tunable parameters that align theoretical predictions with observed performance.